Development of a Xeno-Free Substrate for Human Embryonic Stem Cell Growth. (16th March 2015) - Zhu, Hailin; Yang, Jinliang; Wei, Yuquan; Chen, Harry Huimin
Abstract : Traditionally, human embryonic stem cells (hESCs) are cultured on inactivated live feeder cells. For clinical application using hESCs, there is a requirement to minimize the risk of contamination with animal components. Extracellular matrix (ECM) derived from feeder cells is the most natural way to provide xeno-free substrates for hESC growth. In this study, we optimized the step-by-step procedure for ECM processing to develop a xeno-free ECM that supports the growth of undifferentiated hESCs. In addition, this newly developed xeno-free substrate can be stored at 4°C and is ready to use upon request, which serves as an easier way to amplify hESCs for clinical applications.